Toma de decisiones preinteractivas de profesores de educación física (Planning Decisions of Physical Education Teachers) - Piéron, Maurice; Cloes, Marc (Retos, 2007)
Cuarenta y seis profesores participaron en el estudio. Entre ellos, 27 teniendo una experiencia de enseñanza de más de cinco años (12mujeres y 15 hombres) y 19 principiantes (12 mujeres y 7 hombres). Contestaron a cinco escenarios en el marco de una entrevista  requerían de decisiones a medio plazo.. Se recogieron y analizaron 434 propuestas de acción dado que una respuesta podía tener muchas propuestas diferentes. Las acciones propuestas fueron analizadas desde registros audio de las entrevistas con profesores. Fueron clasificadas de una manera inductiva. Las opiniones de los profesores con experiencia, hombres y mujeres, son más diversas que aquéllas de sus colegas principiantes, como lo atestigua el gran número de categorías diferentes. Cuatro categorías de decisiones tratan del contenido de la enseñanza: «adaptación de los ejercicios al alumno», «creación de grupos de niveles», «gradación de la dificultad», «misma actividad para todos.» Los profesores interrogados disponen inmediatamente de estrategias disponibles para tratar las diferencias individuales de los alumnos. Según sus características personales, los profesores sugieren preferentemente intervenciones específicas.Abstract: Forty-six PE teachers participated in the study. Among them, 27 had an experience of more than five years in teaching (12 women and15 men) and 19 beginning teachers (12 women and 7 men). Teachers were presented five scenarios of instructional situations. They were asked to readeach scenario and write a response detailing how they would react if the situation occurred during their teaching. Four hundred thirty-four proposalsof actions were gathered and analysed since an answer could have many different proposals. The actions proposed were analysed from audiotapes ofteachers’ interviews. They were classified according to an inductive technique. The opinions of experienced teachers, men and women, differed thanthose of their beginning colleagues, as indicated by the number and content of categories. Four categories of decisions dealt with the content ofeducation: «adaptation of the exercises to the student», «creation of levels groups», «gradation of the difficulty», and «same activity for all.» Theteachers had strategies immediately available to deal with the students’ individual differences. According to their personal characteristics, experiencedteachers displayed a greater variety of application of sound principles of teaching.